Paralelos: vidas erguidas pelo esporte adaptado - Martins, Maria Paula (2020)
This paper reports the process of producing the non-fiction book PARALLELS: lives raised by the adapted sport. We started from the following question: how do the media and Brazilian society build the image of people with disabilities? Based on the guiding question, the general objective of this work was to produce a book-report with profiles, biographical and descriptive texts of four parathletes weightlifters from Uberlandia (MG) – and which have relevance in the national sports scene. At a time when the news climbs increasingly dynamic, express and fast-consuming steps, we invest in literary journalism as a way to deepen and humanize. Therefore, the intention here is to give more visibility to this theme, by having Lara Lima, Gilvan Santos, Amanda Sousa and Mateus Assis as protagonists of their own stories.